What Mathematics Matters to Teachers? - Gandhi, Haneet (Voices of Teachers and Teacher Educators, 2016)
This article draws attention to the need of mathematising the teacher of mathematics. The paper questions and seek answers to the didactical approaches that should be adopted to engage teachers in acts of thinking mathematically. One of the proposed ways is by challenging teachers’ existing mathematical cognition in a constructive manner. The paper further elaborates a task that was instrumental in setting up conditions for thinking, reasoning and making conceptual connections.